PTU-006 Gastroenterology Trainees Express An Interest To Learn To Perform Ultrasound-assisted Liver Biopsies: Results Of A National Survey (uk). (9th June 2014) - Dolman, GE; Austin, A
Abstract : Introduction: Liver biopsy for the assessment of parenchymal liver disease is increasingly performed under direct ultrasound guidance by radiologists. As such, it is no longer a mandatory requirement for hepatology trainees in the UK to achieve competence in this procedure. Methods: We aimed to determine whether trainees are receiving training to perform ultrasound-assisted liver biopsies; and whether they would be interested in doing so if not. Trainees anonymously responded to a 10 question, web based survey using a combination of pre-defined answers in drop down boxes and free text answers. Results: Surveys were sent to approximately 800 trainees. 226 surveys were returned. Respondents represented all training grades (ST3-ST7). 75 respondents (33%) intend to pursue subspecialty accreditation in hepatology. 103 respondents (46%) have completed a period of training in a tertiary/transplant centre. 105 respondents (47%) have worked in a centre where physicians perform liver biopsies. 52 (23%) have been offered the opportunity to learn how to perform ultrasound assisted liver biopsy and 38 (17%) have been assessed and deemed competent in the procedure. Three respondents commented that they are trained in unguided liver biopsy; one trainee has used the Sonosite probe and one commented that he/she has performed liver biopsy after an appropriate site was marked by the radiologist 137 (61%) of trainees who responded to the survey would be interested in learning how to perform this procedure and a further 29 (13%) may be interested. 138 (61%) of respondents would be interested in attending a hands-on course to learn this procedure and 30 (13%) may be interested. Of the 75 respondents who intend to pursue subspecialty hepatology accreditation, 72 said they would be interested in learning how to perform ultrasound assisted liver biopsy. Trainees who participated in this survey reported that opportunities to learn this procedure were currently hit and miss. There were concerns about the practicality of maintaining competence during training and as a consultant and some respondents felt that it was safer for the procedure to be performed by radiologists. We cannot report the views of trainees who did not complete the survey and therefore our results may not be representative. However even if we make the assumption that all non-responders are not interested in learning this procedure, there is still an estimated 15–20% of trainees that would be interested (137/ 800). Conclusion: Trainees participating in this survey are interested in learning to perform ultrasound-assisted liver biopsies, but the infrastructure to offer this training is not currently well established. Discussion between trainees and training bodies should be considered to explore this issue further. Disclosure of Interest: None Declared.